A study and analysis of input output linearization control of permanent magnet synchronous motor based on fuzzy observer - Belbekri, Tahar; Bellali, Badreddine (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
This article describes the nonlinear control of input output linearization type without speed sensor of permanent magnet synchronous motor (PMSM). This machine which has several advantages such as simple structure and high efficiency. Its control requires speed determination by sensor. Due to several disadvantages of using the speed sensor, we replaced it with a so-called Luenberger observer. The simulation results show that the observer considerably improves the performance of the PMSM in particular in overshooting during start-up and during speed reversal. It also shows good robustness when applying load torque. To obtain high operating performance of the PMSM, it basically needs to replace the proportional integral (PI) controller with another controller based on fuzzy logic. This artificial intelligence technique allowed us to obtain more efficient results than the traditional method.